Percepções relativas às práticas em sustentabilidade nos canteiros de obras - Coutinho, Sandra Moscon (2013)
The civil engineering process stands out for being an activity whitch causes major impact to the environment, due to its high consumption of material resources, water and energy, and its high levels of waste and pollution generation. On the other hand, it has significant economic importance and challenges to overcome: like sustainable development, in order to avoid irreparable environmental harm to future generations.Sustainability shoud be inserted throughout the buildinglife cycle, specially in its beginning, whitch means, in the construction site phase, because it is here where occur most of the environmental impacts. In this context, this descriptiveand qualitative research, presents an assessment instrument of perceptions regarding sustainability practices for the construction site phase, consisting of: (a) questionnaire; (b) direct observations list; and (c) photographic records list. The proposed assessment tool was applied to nine case studies, conducted on construction sites, located in the city of Vitória (ES). The application of the assessment instrument aroused interest among those responsible for the construction sites, possibly because this topic is little discussed in the local market. It was observed that, from the perspective of the respondent perceptions, sustainability in the construction site phase is in an incipient form, even though the construction sites visited belongto builders of medium and large sizes, with ISO 9001 certifications, PBQP-H level A and a lot of finalized and under construction buildings